The Use and Impact Socialization of Religious Moderation Values Through Media of Hand Puppet Theater Stages Toward Forming Character of Tolerance In Primary School Students - Rhesti Laila Ulfa; Ikhtiati Ikhtiati; Fia Alifah Putri (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
Indonesia is a country with a rich diversity of religions and cultures. This diversity is a defining characteristic of the Indonesian nation and must be preserved and respected. This research aims to promote values of religious moderation through hand puppet theater performances to shape the tolerance character of elementary school students. Adopting a Participatory Action Research (PAR) methodology, which includes counseling, art performances, group discussions, and material distribution, this research strives for accurate results. The findings of this study will demonstrate the impact and effectiveness of performances in influencing the character of students at MIS Nurul Yaqin. A child's character is significantly shaped by their experiences at home, school, and in their community. This research indicates that the character development of MIS Nurul Yaqin students is influenced by three key aspects: (1) moral knowing, (2) moral feeling, and (3) moral action.